Survey on nodulation of indigenous legume trees in southeast Brazil - Faria, Sergio Miana de (2014)
A survey on nodulation of legume trees was perfomed in (1) Linhares-ES, Reserva Florestal da Companhia Vale do Rio Doce (2) Seropédica-RJ, Estação Florestal de Experimentação Eng°.-Agr°. Mário Xavier and (3) São Paulo, Instituto Florestal de São Paulo. In site (1) and (3) the observations were carried out in the field and with non-inoculated plants in nursery beds, and in place (2) only in nursery beds. The whole root system of young plants or roots attached to old plants were freed of soil, and the nodules assayed individually for nitrogenase activity (C2H2). After the nodule morphology had been observed, the nodules were dried and kept in CaCl2 for Rhizobium isolation. Thirty one out of 43 species of the sub-family Papilionoideae were nodulated, 19 of them reported for the first time. Seven out of 41 species of Caesalpinioideae were nodulated, 6 of them reported for the first time, and 30 out of 35 species of Mimosoideae were nodulated, 11 of them reported for the first time. All the species found with nodules showed nitrogenase activity. Within the new species found with nodules there were 5 genera not reported before: Bowdichia and Poecilanthe (Papilionoideae), Melanoxylon and Moldenhaurea (caesalpinioideae) and Pseudosamanea (Mimosoideae). Among the not nodulating species, 37 had not been reported as such, previously. The nitrogenase activity of individual nodules was variable with species and was in general lower in the species of the sub-family Mimosoideae than the other two sub-families.